Determinación de alteraciones anatomopatológicas de hígados bovinos en el Camal Municipal del cantón Guaranda. - García Macías, Iván Marcelo (2020)
In the Guaranda canton located at 2923 meters above sea level, it was; studied to determine the pathological abnormalities of bovine livers in the municipal road of the Guaranda canton. A descriptive qualitative statistical model was applied. With a sample of 200 livers of slaughtered cattle. Percentages, means, frequency and graph were calculated. The objectives set were: 1) To identify, through post-mortem macroscopic inspection, liver pathological abnormalities. 2) Establish the causes of total seizure of livers and 3) Perform the economic analysis for seizure of infected livers. The variables evaluated and results were; Prevalence, 9% Distomatosis and 1% Hydatidosis in 200 bovine livers; Origin Vinchoa, Guanujo and El Olivo 19%; Viceroy 14%, Guaranda 9% and La Playa, El Peñón, El Castillo and June 5 5%; Age 3 years 47%, 4 years 38%, 2 years 10%, and 5 years 5%; Sex females 71% and males 29%; Mixed race 100%; Liver weight 5.9 kg 18%, 6.7 - 5.8 kg 9% and 8.5 - 5.1 kg 5%; and economic losses, the total weight of the seized livers was 129.6 kg, the commercial price of the kilogram of bovine liver is $ 4.00 USD. Causing loss of $ 518.40 USD. Finally, it follows that this research determined that the prevalence and economic impact of pathological abnormalities in confiscated bovine livers was related by ecological, human, genetic, nutritional factors and pathophysiological characteristics that favored pathological persistence.